The Protection Of Copyright Law (Copyright) In The Piracy Of Creation - Muhammad Fathan Laleno (Universitas Negeri Gorontalo, 2019)
Abstract: Intellectual Rights have now spread to both traditional and modern sectors. In its copyright one of the regulations is copyright. Researchers define copyright itself as one of the rights that govern the ownership of a physical item, where everything related to creation must have permission from the party concerned. The development of technology that is increasingly advanced, causing HAKI itself to adjust to the changes that occur, the use of e-books is one of the results of technological developments that are increasingly advanced over time. The results of research related to the Article entitled Legal Protection of The Creator's Economic Rights in The Doubling of Creation are expected to be a consideration and benchmark for existing copyright.Keywords: Intellectual Property Rights; Copyright; Piracy.